A kinetic study of carotenoid degradation during storage of papaya chips obtained by vacuum frying with saturated and unsaturated oils. (February 2020) - Soto, Marvin; Dhuique-Mayer, Claudie; Servent, Adrien; Jiménez, Nadiarid; Vaillant, Fabrice; Achir, Nawel
Graphical abstract: Highlights: Vacuum fried papaya chips contain 128 mg·kg −1 lycopene (82% of total carotenoids). Carotenoid degradation follows 2nd order kinetic and Arrhenius model during storage. Packaging of papaya chips with N2 avoided carotenoid degradation. Lycopene was the most stable carotenoid in papaya chips during storage. Type and oil content influenced carotenoid content and nutritional quality of chips. Abstract: The aim of the study was to evaluate the degradation kinetics of carotenoids (CTs) in vacuum-fried papaya ( Carica papaya L.) chips (PCs) during storage at four temperatures (15, 25, 35 and 45 °C) for 52 and 94 days for the two highest and lowest temperatures, respectively. Three treatments were applied to obtain the chips: chips with soy oil (24% lipids) and chips with palm oil (24% and 29% lipids). All the chips were packaged under air or nitrogen conditions. The CTs analyzed by HPLC-DAD were per order of content all-E-lycopene (LYC), Z-lycopene (Z-LYC), all-E-β-carotene (BC), all-E-β-cryptoxanthin (BCX) and Z-β-carotene (Z-BC). The all-E-forms represented 80% of carotenoids in PCs. No significant carotenoid degradation was observed in the PCs packaged under nitrogen conditions during storage. For chips stored under air conditions, a second-order kinetic model best fitted the experimental data. Rate constants for LYC degradation were the lowest, while BCX and BC presented similar rate constants 4–23-fold higher depending on lipid composition. All Z - isomers degraded faster than all-E - forms, but Z-BC degraded only 2–4-fold faster than Z-LYC. All CTs followed Arrhenius temperature-dependency pattern and LYC showed the lowest activation energies (5–21 kJ/mol). A higher lipid content in the chips with palm oil enhanced the carotenoid retention in PCs. Moreover, a greater retention (p < 0.05) of CTs was observed in PCs with soy oil. The use of soy oil instead of palm oil increased the theoretical half-life (at 25 °C) by 2.2, 1.3 and 5.9-fold for BCX, BC and LYC, respectively. Packaging under nitrogen conditions and lipid composition may be considered to optimize the shelf life and carotenoid retention in PCs during storage.